Asuhan Keperawatan pada Klien An “F” dengan Trauma Capitis di Ruang ICU RSUD Labuang Baji Makassar - Tuty Alawiyah Alimuddin; Alwi Ismail; Amiruddin J (Jurnal Sains dan Kesehatan, 2021)
Trauma capitis is a form of penetration or rapid movement, and impact of the brain within the skull which results in changes in mental status. Traumatic capitis is one of the causes of child death. Often referred to as the silent. The aim of this research is to obtain a real picture in applying nursing care to clients An.''F'' with cases of neurological system disorders: trauma capitis. This research was carried out in the ICU room at Labuang Baji Hospital, Makassar for 3 days starting from 19-21 April 2023. Data collection techniques were carried out using interview techniques, observation and physical examination. The results of this study were an assessment of pain in the head, pain that felt like stabbing, pain scale 8 (severity 0-10), lasted for 3 minutes, bleeding on the right side of the head. In nursing diagnoses, there are 5 diagnoses found in cases of acute pain related to physical comfort, ineffective breathing patterns related to changes in the depth of breathing patterns, risk of infection related to bleeding in the brain, nutritional imbalances less than body requirements related to lack of appetite, impaired mobility physical related to difficulty turning positions. In implementing the action plan for patient An "F", nursing problems arise to reduce and prevent problems in patients by paying attention to the patient's condition. The implementation of nursing for patient An "F" is adjusted to the action plan that has been determined so that the nursing problems faced by the patient can be overcome or prevented. After providing nursing care for the five diagnoses, all diagnoses were resolved.